Novas tecnologias e infraestrutura do setor elétrico brasileiro: Armazenamento de energia em baterias - Rogério Diogne de Souza E Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
Battery Energy Storage Systems (BESS) have been implemented in the various systems of the electric sector, from the basic network to the consumer, such scope demands different business models and regulatory structure. In Brazil, the regulatory agenda should include energy storage as an ancillary service, the creation of the distribution system operator model, the aggregating agent service to enable virtual plants, and, on the demand side, the charging and discharging models of batteries involving the supply or compensation of electricity with the distribution concessionaire. In this context, the present study addresses battery storage technologies, the state-of-the-art, the respective applications in the electric sector, the international and Brazilian scenario, aiming to discuss the necessary actions, aspects related to regulation and policies, and how these new technologies can direct the planning of the infrastructure of the electric sector in Brazil.
Keywords: L94; 330; energy storage; batteries; electric sector; energy transition